Fifty chairs that changed the world : design museum - Czerwinski, Michael; Design Museum (London, England) (London : Conran Octopus, 2009)
Everything around us is designed and the word 'design' has become part of our everyday experience. But how much do we know about it? This book imparts that knowledge, listing the top 50 chairs that have made a substantial impact in the world of design. It includes entries from Thonet's 1870 Side Chair to Konstantin Grcic's Chair_One
Includes index
Keywords: Chair design -- History; Chairs; Chairs -- Pictorial works